An analytical model of threshold voltage for short-channel double-material-gate (DMG) strained-Si (s-Si) on Silicon-Germanium-on-Insulator (SGOI) MOSFETs - Kumar M.; Dubey S.; Tiwari P.K.; Jit S. (My University, 2025)
In this paper, an analytical short-channel threshold voltage model is presented for double-material-gate (DMG) strained-Si (s-Si) on Silicon-Germanium-on-Insulator (SGOI) MOSFETs. The threshold voltage model is based on the "virtual cathode" concept which is determined by the two-dimensional (2D) channel potential of the device. The channel potential has been determined by solving 2D Poisson's equation with suitable boundary conditions in both the strained-Si layer and relaxed Si1-x Ge x layer. The effects of various device parameters like Ge mole fraction, Si film thickness, SiGe thickness and gate-length ratio have been considered on threshold voltage. Further, the drain induced barrier lowering (DIBL) has also been estimated. The validity of the present 2D analytical model is verified by using ATLAS™, a 2D device simulator from Silvaco. © 2012 Springer Science+Business Media New York.